Peningkatan Kemampuan Pemahaman Konsep dan Komunikasi Matematis Siswa Dengan Menggunakan Pembelajaran Kooperatif Tipe Jigsaw - Widyastuti, Eri (AlphaMath : Journal of Mathematics Education, 2015)
The purposes of this study to determine: (1) The different improvement of students proficiency of mathematics understanding who were taught through STAD, Jigsaw and the students who were taught through conventional study, (2) The different improvement of students proficiency of mathematics understanding who were taught through STAD, Jigsaw and the students who were taught through conventional study, (3) How the process of problem solving by the students who were taught through STAD, Jigsaw and conventional study. This research was aquasi-experimental study. This study population of this study are the students of XI IPA in Medan. The school are selected randomly as the subjects research, those are SMA Negeri 17 Medan and SMA Dharma Pancasila Medan. The first experimental class was treated by STAD, the second experimental class was treated by Jigsaw and the control class was treated by conventional study. The instruments used consist of: (1) The proficiency test of mathematics understanding, (2) The proficiency test of mathematics communication and (3) The observation sheet. These instruments have fullfilled the essential of content validity and reliability coefficient used were 0.91 and 0.91 for mathematics understanding and mathematics communication. The data analysis was done by using variance analysis (ANAVA). The results showed that (1) The different improvement of students proficiency of mathematics understanding who were taught through STAD, Jigsaw and the students who were taught through conventional study, (2) The different improvement of students proficiency of mathematics understanding who were taught through STAD, Jigsaw and the students who were taught through conventional study, (3) The process of problem solving by the students who were taught through STAD, Jigsaw have many variations if it was compared by the process of problem solving by the students who were taught through conventional study. Keywords : Cooperative Learning with STAD and Jigsaw, Mathematics Understanding and Mathematics Communication.